2D Metamaterials: Designing Mechanical Metamaterials with Kirigami‐Inspired, Hierarchical Constructions for Giant Positive and Negative Thermal Expansion (Adv. Mater. 3/2021). Issue 3 (19th January 2021) - Guo, Xiaogang; Ni, Xiaoyue; Li, Jiahong; Zhang, Hang; Zhang, Fan; Yu, Huabin; Wu, Jun; Bai, Yun; Lei, Hongshuai; Huang, Yonggang; Rogers, John A.; Zhang, Yihui
Abstract : In article number 2004919, John A. Rogers, Yihui Zhang, and co‐workers present design concepts and fabrication strategies for a kirigami‐inspired class of 2D hierarchical metamaterials. At large filling ratios (>50%), these systems offer not only unprecedented biaxial CTE (i.e., −5950 and 10710 ppm K −1 ), but also large biaxial thermal expansion properties (>21% for 20 K temperature increase), unachievable previously.